1999
DOI: 10.1021/ol990108n
|View full text |Cite
|
Sign up to set email alerts
|

Core-Modified Smaragdyrins:  First Examples of Stable Meso-Substituted Expanded Corrole

Abstract: A synthetic access to the first members of expanded corroles 1 and 2 is achieved through formation of two direct pyrrole−pyrrole links by an oxidative coupling reaction. Spectroscopic and structural analysis reveal that 1 and 2 are 22Π aromatic macrocycles despite the nonplanar structure and properties resemble that of isocorroles rather than 22Π sapphyrins. Sapphyrin 1 is an example of the simplest possible expanded porphyrin with 22Π electrons. 1 The existence of sapphyrins was been reported long ago, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 15 publications
(17 reference statements)
1
86
0
1
Order By: Relevance
“…[61] For example, an oxidative coupling between the heterotripyrranes 43 and the dipyrromethane 42 gives rise to heterosmaragdyrins (Scheme 6). In the case of the oxasmaragdyrin 44 b (Ar = Ph), the reported yields are as high as 51 %, while for the corresponding thiasmaragdyrins, the yields are significantly lower, namely, 5 % for 44 a (Ar = Ph).…”
Section: Heteroatom-containing Smaragdyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] For example, an oxidative coupling between the heterotripyrranes 43 and the dipyrromethane 42 gives rise to heterosmaragdyrins (Scheme 6). In the case of the oxasmaragdyrin 44 b (Ar = Ph), the reported yields are as high as 51 %, while for the corresponding thiasmaragdyrins, the yields are significantly lower, namely, 5 % for 44 a (Ar = Ph).…”
Section: Heteroatom-containing Smaragdyrinsmentioning
confidence: 99%
“…Catalytic decomposition of peroxynitrite by a manganesetexaphyrin complex. [61] Expanded Porphyrins Angewandte Chemie Figure 15. In the same report, the possibility of using the protonated form of 44 b as an anion receptor was also noted (see Figure 16 for the X-ray structure).…”
Section: Heteroatom-containing Smaragdyrinsmentioning
confidence: 99%
“…Recently, Chandrashekar and co-workers have demonstrated that the R-R coupling of 5,10-diphenyl-16-oxatripyrrane and dipyrromethane yields 5,10,15-triaryl-21-oxacorrole. 32, 33 Lindsey and co-workers have remarked that the condensation of 5-(p-tolyl)-dipyrromethane and furylpyrromethanediol yielded 5,10,15-triaryloxacorrole in addition to the expected 5,10,15,20-tetraaryl-21-oxaporphyrin. 34 Lee and co-workers have reported on an original way to produce 5,10,15-triaryl-21-oxacorrole and, for the first time, the isomeric 5,10,15-triaryl-22-oxacorrole. 35 Finally, the Vogel group succeeded 36,37 in preparation of tetraoxacorrole cation and octaethyltetroxacorrole cation, although these results are practically available in the review articles.…”
Section: Introductionmentioning
confidence: 99%
“…Chandrashekar and co-workers found that the acid-catalyzed coupling of dipyrromethane 23 and 16-oxatripyrrane 24 catalyzed by BF 3 ·OEt 2 leads, in addition to the expected core-modified smaragdyrin (26), also to core-modified corrole 25 as a side product (Scheme 12). [51] The formation of core-modified corroles in this [3ϩ2] reaction is due to the fact that both substrates are susceptible to acid-catalyzed rearrangements and are known to undergo fragmentation.…”
Section: Core-modified Corrolesmentioning
confidence: 99%
“…[52] Complexes of oxacorroles with Cu II , Ni, II or Co II have already been prepared by reaction with CuCl 2 , NiCl 2 , or Co-(OAc) 2 in DMF. [51] The chemistry of triazatetrabenzocorroles, first obtained by Fujiki et al, [53] was recently further developed by Hanack and co-workers. They found that reaction of diiminoisoindoline 31 with Si 2 Cl 6 leads to the ring-contracted (hydroxy)(α,β,γ-triazatetrabenzocorrole)silicon 32 (Scheme 14).…”
Section: Core-modified Corrolesmentioning
confidence: 99%